2014
DOI: 10.1093/heapro/dau047
|View full text |Cite
|
Sign up to set email alerts
|

Intersectoral action: local governments promoting health

Abstract: Many local governments around the world promote health through intersectoral action, but to date there has been little systematic evidence of these experiences. To bridge this gap, the World Health Organization Centre for Health Development conducted a study in 2011-2013 on intersectoral action for health (ISA) at local government level. A total of 25 cases were included in the final review. Various approaches were used to carry out ISA by local governments in low-, middle- and high-income countries. Several c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 6 publications
5
65
0
15
Order By: Relevance
“…While ideas about ISA are generally popular, their implementation have been difficult (Hendriks et al, 2013;Ollila, 2011; Public Health Agency of Canada [PHAC], 2007). A growing body of scholarly literature addresses the lack of ISA implementation, typically by exploring barriers and facilitators as well as strategies for (better) implementation (Berkeley & Springett, 2006;Freiler et al, 2013;Hendriks et al, 2013;Larsen, Rantala, Koudenburg & Gulis, 2014;Rantala, Bortz & Armada, 2014;Ollila, 2011). Governance structures, political leadership and capacity building are common themes, often with an instrumentalist ambition to advance the ability of public health professionals to engage other sectors in collaboration to promote health (Embrett & Randall, 2014;McQueen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While ideas about ISA are generally popular, their implementation have been difficult (Hendriks et al, 2013;Ollila, 2011; Public Health Agency of Canada [PHAC], 2007). A growing body of scholarly literature addresses the lack of ISA implementation, typically by exploring barriers and facilitators as well as strategies for (better) implementation (Berkeley & Springett, 2006;Freiler et al, 2013;Hendriks et al, 2013;Larsen, Rantala, Koudenburg & Gulis, 2014;Rantala, Bortz & Armada, 2014;Ollila, 2011). Governance structures, political leadership and capacity building are common themes, often with an instrumentalist ambition to advance the ability of public health professionals to engage other sectors in collaboration to promote health (Embrett & Randall, 2014;McQueen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…investing in collaborative relationships; and agreeing on criteria for success (20). Similar recommendations can be found in reviews throughout the literature, many of which also draw substantially from case studies (5)(6)(7)(8)10,11,13,(21)(22)(23)(24)(25)(26).…”
Section: Figure 4: Distribution Of Research Methods On Msc By Topicalmentioning
confidence: 73%
“…Thus, it has created the National Policy for the Monitoring and Evaluation of Primary Care 23 , and it has stimulated family health teams to perform M&E actions through the Programa Nacional de Melhoria do Acesso e da Qualidade da Atenção Básica (PMAQ-AB 24 -National Program to Improve the Access to and the Quality of Primary Care). In the international context, a study developed by the WHO 25 analyzed 25 cases of health promotion interventions developed by the local governments of 19 countries and showed that the majority of these interventions mentioned the use of evaluation as a strategy to monitor the results of interventions. Moreover, this study highlighted the importance of the participation of universities or research institutions in the local governments' support to the performance of M&E actions in interventions.…”
Section: Discussionmentioning
confidence: 99%